Analysis of Embroidery and Sequin Decoration Results on Party Dresses by Fashion Designer Riki Damanik - Aqilah Putri; Dina Ampera (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to determine the embroidery and sequin decoration techniques on party dresses at the Riki Damanik boutique. The method used is the Qualitative Research Method. The data collection tools used are interviews and observations. The results of the study indicate that the embroidery and sequin decoration techniques applied at the Riki Damanik Boutique combine manual and machine processes to produce clothes with an elegant and exclusive appearance. The embroidery and sequin decorations applied not only function as aesthetic elements but also add to the durability of the party dress. The combination of high-quality materials and careful workmanship techniques make this boutique's products more valuable than similar products on the market. Party dresses with embroidery and sequins from this boutique not only follow fashion trends but also offer a distinctive identity that distinguishes them from competitors. The selection of detailed motifs, colors, and workmanship techniques is a special attraction for customers who want clothes with high artistic value. Researchers are looking for innovation and sequin installation techniques to be more economical without reducing quality and durability. Despite facing several challenges in production, this boutique has great potential to continue to grow with innovative strategies in design, production efficiency, and marketing. By maintaining quality and following fashion trends, boutiques can continue to attract customers who want exclusive party wear with luxurious touches of embroidery and sequins.